The teaching of philosophy in public administration programmes. Issue 2 (July 2019) - Ongaro, Edoardo
Public administration can be considered as an applied, interdisciplinary field, whose study demands the contribution of a range of disciplines, including political science, management, law, sociology and others. The article argues that the disciplines of public administration should also include philosophy, not as a discipline (philosophy is not a discipline in the sense modern sciences are; rather, at the roots of philosophy are key questions: what there is (ontology); who we are (philosophy of the mind); how to live well (ethics); how to live well together (political philosophy) and so on) but as the foundation of all the other disciplines studying public administration, from political science (whose roots are in political philosophy), to management and sociology (whose underpinnings are in ontological conceptions of the individual and society), to law (whose roots are in the philosophy of law) and so on. If philosophy is foundational to public administration, then two key questions arise: in researching public administration, what is the contribution of philosophy to advancing our understanding of public administration? And in the teaching of public administration, what is the place of philosophy in the curricula of public administration programmes? The article, after briefly reviewing the philosophical foundations of public administration, aims to discuss the latter question about the contribution of philosophy to educational and training programmes in the field of public administration, and the place of philosophy in public administration education curricula.